A de novo missense variant in GABRA4 alters receptor function in an epileptic and neurodevelopmental phenotype. Issue 4 (12th February 2022) - Vogel, Florian D.; Krenn, Martin; Westphal, Dominik S.; Graf, Elisabeth; Wagner, Matias; Leiz, Steffen; Koniuszewski, Filip; Augé‐Stock, Maximilian; Kramer, Georg; Scholze, Petra; Ernst, Margot
Abstract: Variants in γ‐aminobutyric acid A (GABAA ) receptor genes cause different forms of epilepsy and neurodevelopmental disorders. To date, GABRA4, encoding the α4‐subunit, has not been associated with a monogenic condition. However, preclinical evidence points toward seizure susceptibility. Here, we report a de novo missense variant in GABRA4 (c.899C>T, p.Thr300Ile) in an individual with early‐onset drug‐resistant epilepsy and neurodevelopmental abnormalities. An electrophysiological characterization of the variant, which is located in the pore‐forming domain, shows accelerated desensitization and a lack of seizure‐protective neurosteroid function. In conclusion, our findings strongly suggest an association between de novo variation in GABRA4 and a neurodevelopmental disorder with epilepsy.